2019
DOI: 10.1016/j.energy.2019.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the electricity saving potential of electrochromic glazing for cooling and lighting at the scale of the Swiss non-residential national building stock using a Monte Carlo model

Abstract: Novel electrochromic glazing technology has been identified as an emerging option for reducing cooling and lighting electricity demand. As this technology is particularly promising for office building we assess the related technical energy saving potential in case of nationwide implementation in Swiss office buildings. A Monte Carlo model of Swiss office building stock using distributions of empirical building characteristics was coupled with a statistical model of energy savings of electrochromic glazing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Haarhoff and Mathews [11] presented a simplified Monte Carlo method for finding an approximation of the temperature distribution inside a building, the results show that relatively accurate results can be obtained with very little data. Chambers et al [12] used a Monte Carlo model to evaluate the effect of color-changing glass on energy saving potential. Sørensen et al [13] used a Monte Carlo simulation to model the energy performance and indoor climate of buildings considering building physical parameters, including properties of facades, walls, windows, etc., and sift through thousands of combinations of these parameters to find those that meet design criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Haarhoff and Mathews [11] presented a simplified Monte Carlo method for finding an approximation of the temperature distribution inside a building, the results show that relatively accurate results can be obtained with very little data. Chambers et al [12] used a Monte Carlo model to evaluate the effect of color-changing glass on energy saving potential. Sørensen et al [13] used a Monte Carlo simulation to model the energy performance and indoor climate of buildings considering building physical parameters, including properties of facades, walls, windows, etc., and sift through thousands of combinations of these parameters to find those that meet design criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most buildings have large windows and glass facades-jointly known as glazing-and means to improve those clearly can have an important impact on energy use. Dynamic or "smart" glazing, with variable optical properties, has been studied recently from an energy perspective, and it has been demonstrated that significant energy savings are indeed possible [3][4][5][6]; market research has identified electrochromic (EC) glazing as the most viable technology for dynamic glazing [7].…”
Section: Introductionmentioning
confidence: 99%
“…EC smart windows showed great energy saving potentials for Swiss office buildings and showed 11% energy saving potential in lighting and cooling demand [21]. Fang et al [22] evaluated thermal performance of an EC window and results of their research showed that EC windows could absorb 60% of solar radiation in their tinted state.…”
Section: Introductionmentioning
confidence: 99%